RESPONSE OF IRRIGATED LOWLAND RICE (ORYZA SATIVA L.) TO DIFFERENT LEVELS OF INORGANIC FERTILIZER SUPPLEMENTED WITH VERMITEA - Vinculado, Editho C; Cagasan, Ulysses A (Journal of Agriculture and Technology Management, 2021)
This study was conducted to determine the appropriate levels and assess the economic profitability of rice production per hectare using inorganic fertilizer supplemented with vermitea. The experimental area was laid out in a Randomized Complete Block Design (RCBD) with three (3) replications. Each replication was divided into five (5) treatment plots, each measuring twenty (20 m 2 ), separated by 1.0 m and 0.5 m alleyways between replications and treatments. The following treatments designated were as follows: T 0 = No fertilizer (Control); T1 = 90-60-60 kg ha -1 N, P2O5, and K2O (General RR of inorganic fertilizer); T 2 = 90-60-60 kg ha - 1 N, P 2 O 5 , K 2 O + Vermitea; T 3 = 70-40-40 kg ha -1 N, P 2 O 5 , K 2 O + Vermitea; T 4 = 50-30-30 kg ha -1 N, P 2 O 5 , K 2 O + Vermitea. Results revealed that most of the agronomic characteristics of Matatag 6 variety were significantly influenced by the treatments except the number of days from sowing to heading. Rice plants applied with 70-40-40 kg ha -1 N, P 2 O 5 , K 2 O were comparable with the recommended rate at 90-60-60 kg ha -1 N, P 2 O 5 , K 2 O. This treatment (T 3 ) obtained the highest net Income of (PhP44,995.99), significantly similar to rice plants applied with the recommended rate of fertilizer (T 1 ) at PhP 44,893.77. While rice plants not applied with fertilizer got the lowest net income of PhP 23,100.00 because of the low yield per hectare. Thus, Matatag 6 rice variety can be grown with a minimum inorganic fertilizer application of 70-40-40 kg ha -1 N, P 2 O 5 , K 2 O provided that vermitea will be applied.